STRATEGI PENGEMBANGAN AGRIBISNIS SALAK NGLUMUT BERSERTIFIKAT PRIMA 3 DI KABUPATEN MAGELANG - Suharso Suharso; Anang M Legowo; Agus Setiadi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
The business of Nglumut’s Salak in Magelang district have significant value to increase the security of population, and the expansion of Nglunut’s Salak agribusiness is very productive. In an effort to increase the production and the quality of fruit in sufficient quantity and safe to eat and are produced with observe the environmental sustainability, then require of reflection as the basic of policy with real action. Therefore the expansion strategy of Nglumut’s Salak agribusiness have reach must be aadapted to the characteristics and problems of the agribusiness concerned. The expansion strategy of Nglumut’s Salak is certified “Prima 3” will be able to keep the competitiveness and the existence of the business. This study was aimed to determine a) sub system agribusiness of Salak Nglumut Prime 3 Certified in Magelang Regency b) the priority of agribusiness development strategy of Salak Nglumut Prime 3 Certified in Magelang Regency. This study was conducted in Kamongan, Kaliurang, Nglumut Kradenan village in Srumbung Sub Districts. The research was conducted from Aprill to June 2015. Respondents as key persons consisted of 30 respondent that were taken purposively. Method of data analysis used in this study was alternative strategy priority was analyzed by using AHP (Analytical Hierarchy Process) with expert choice program. Based on AHP analysis, The three main priorities of agribusiness development strategy of Salak Nglumut is as follows: 1) improvement of product quality, 2) business development, 3) strengthening of the market. Alternative priority strategies of agribusiness development of Salak Nglumut Prime 3 Certified is 1) Application of product standardization (uniformity of quality and size salak 2) The certification and product labeling; 3) cultivation technology and management efforts are directed using good farming guidelines (Good Agricultural Practice) towards Prime 3 certified product; 4) Optimization of post-harvest handling; 5) To promote cooperation and improve the business partners; 6) Institutional development; 7) promotion and social networking; 8) The orientation of the export market.